Exposure‐response relationships of etrolizumab in patients with moderately‐to‐severely active ulcerative colitis. (18th July 2022) - Kassir, Nastya; Zhu, Rui; Moein, Anita; Langenhorst, Jurgen; Ribbing, Jakob; Zhang, Rong; Tang, Meina T.; Oh, Young S.; Zhang, Wenhui
Abstract: Etrolizumab is an IgG1‐humanized monoclonal anti‐β7 integrin antibody. Phase III trials with induction and/or maintenance phases were conducted in patients with moderately‐to‐severely active ulcerative colitis (UC) who were either previously treated with tumor necrosis factor (TNF) inhibitors (HICKORY) or were TNF inhibitor naïve (HIBISCUS I/II, LAUREL, and GARDENIA). A total of eight exposure‐response analyses were conducted for two clinical outcomes (remission and endoscopic improvement) at the end of induction for studies HIBISCUS I/II (combined) and HICKORY and at the end of maintenance for studies HICKORY and LAUREL. Trough concentration at week 4 ( C trough, wk4 ) of induction was selected as the exposure metric. Exposure‐response (ER) modeling was conducted using logistic regression. A full covariate model was used to examine the impact of covariates on clinical outcomes. Linear models with a single intercept for placebo and active treatments adequately described the data for all eight analyses. The etrolizumab exposure‐response slope was significant ( p  < 0.05) for seven of the eight analyses. Baseline Mayo Clinic Score (MCS) was the only statistically significant covariate that impacted induction remission and endoscopic improvement. No statistically significant covariate was identified to impact maintenance outcomes except for baseline fecal calprotectin on endoscopic improvement for LAUREL study. A statistically significant positive ER relationship was identified for most of the clinical outcomes tested, reflecting a better treatment effect in patients with UC with higher etrolizumab C trough, wk4 of induction. Baseline MCS was the only other significant covariate impacting induction efficacy. Besides C trough, wk4 of induction, no consistent covariate was identified to impact maintenance efficacy.